Mapping the Poverty Rate of The South Sulawesi Region - Said Muh; Padli Feri; Zulfadli Muhammad; Balqis Syarifah (SHS Web of Conferences, 2022)
This research purpose to presenting information on a smaller regional scale and comparing the conditions of each region. Researchers conducted a poverty mapping technique based on geospatial information. Utilizing the Geographic Information System (GIS) application, namely ArcMap with conversion tools techniques. Data collection techniques with literature study. The poverty level data is processed into tabulation form in the excel application. Meanwhile, the regional base map is first input into the ArcMap application to overlay all regions in one province. The product is a map of the poverty level of the district/city community in the administrative area of South Sulawesi Province. The map will show an image of the area by color category. The dark color gradation means the area with the highest poverty rate and the lightest color means the area with the lowest poverty rate. The results obtained indicate that the districts with the highest poverty rates are Makassar City and Bone District. Meanwhile, the areas with the lowest poverty rates are Barru Regency, Sidenreng Rappang Regency, Pare-Pare City and Palopo City.